The level of competitiveness of the Islamic Digital Economy in Indonesia - Muhajir Muhajir; Abd Kadir Arno (LAA MAISYIR: Jurnal Ekonomi Islam, 2020)
The purpose of this study is to analyze the competitiveness of the Islamic digital economy in Indonesia. This type of research is qualitative. Researchers conducted a comparative analysis using the Diamond Porter model as an analytical instrument. The data was collected using the library research method, which collects library data in the form of books, articles, government or private reports, and other papers containing theories of thought and are relevant to the research variables studied. The results show that based on the diamond porter model, the Islamic digital economy is supported by 1) condition factors, 2) demand factors, 3) related and supportive industries, 4) strategy, structure, and business competition, 5) government, 6) opportunities. The support of these six indicators has a reasonably high impact on the competitiveness of the Islamic digital economy and can continue to develop in the future.